2011
DOI: 10.1128/aac.00291-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of E1210, a Novel Antifungal, against Clinically Important Yeasts and Molds

Abstract: E1210 is a new antifungal compound with a novel mechanism of action and broad spectrum of antifungal activity. We investigated the in vitro antifungal activities of E1210 compared to those of fluconazole, itraconazole, voriconazole, amphotericin B, and micafungin against clinical fungal isolates. E1210 showed potent activities against most Candida spp. (MIC 90 of <0.008 to 0.06 g/ml), except for Candida krusei (MICs of 2 to >32 g/ml). E1210 showed equally potent activities against fluconazole-resistant and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
162
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 23 publications
5
162
1
2
Order By: Relevance
“…YW3548, a natural product, is thought to inhibit the addition of phosphoethanolamine (EtNP) to the first mannose of GPI, but it inhibits both yeast and mammalian GPI-EtNP transferases, although EtNP modification of the first mannose is not essential for the surface expression of GPI-anchored proteins on mammalian cells (22,58). We have modified the prototype compound BIQ (38,59,63) and developed E1210, which possesses potent antifungal activity (19,34). In this study, E1210 was shown to inhibit C. albicans and A. fumigatus Gwt1ps, which are suggested to be involved in the inositol acylation of GlcN-PI in the GPI biosynthesis pathway (36,63,64), but not human Pig-Wp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…YW3548, a natural product, is thought to inhibit the addition of phosphoethanolamine (EtNP) to the first mannose of GPI, but it inhibits both yeast and mammalian GPI-EtNP transferases, although EtNP modification of the first mannose is not essential for the surface expression of GPI-anchored proteins on mammalian cells (22,58). We have modified the prototype compound BIQ (38,59,63) and developed E1210, which possesses potent antifungal activity (19,34). In this study, E1210 was shown to inhibit C. albicans and A. fumigatus Gwt1ps, which are suggested to be involved in the inositol acylation of GlcN-PI in the GPI biosynthesis pathway (36,63,64), but not human Pig-Wp.…”
Section: Discussionmentioning
confidence: 99%
“…E1210 was as active against C. albicans in biofilms as micafungin and amphotericin B, which are fungicidal agents against C. albicans. The antifungal activity of E1210 is fungistatic (34), but E1210 may be expected to indirectly kill Candida cells in hosts, since the deficiency of GPI reduced the resistance of C. albicans to macrophages (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E1210 is a broad spectrum antifungal agent against different pathogenic fungi, including Candida , Aspergillus , Fusarium , and Scedosporium species (190)(191)(192)(193). Importantly, the compound seems to be fungal specifi c and does not inhibit mammalian GPI inositol acylase PIG-W activity ( 194 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…В экспериментальных моделях пока-зано, что этот препарат отличается свойством снижать повреждающее действие аспергилл на ткани, которое превосходит по силе воздей-ствия азолы и амфотерицин В in vitro. Кроме того, показана более выраженная активность против Scedosporium spp., включая S. prolificans (этот вид резистентен почти ко всем известным антифунгальным препаратам), по сравнению с позаконазолом и вориконазолом [17,27,28]. Разрабатывается новая улучшенная форма су-спензии итраконазола и позаконазол для при-ема внутрь с более высокой биодоступностью.…”
unclassified